Marketing Strategy For Banana Chips During Covid-19 (Case Study Of Simple UD In Konda District, South Konawe Regency) - Putri Ayu; Idrus Salam; Hidrawati Hidrawati (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to (1) find out the internal and external factors that are strengths, weaknesses, opportunities, and threats in the marketing of UD. Sederhana banana chips during the Covid-19 pandemic in Konda District, South Konawe Regency, (2) know the marketing strategy of UD banana chips. Simple during the Covid-19 pandemic in Konda District, South Konawe Regency. This research is a case study design research in the UD home industry. Simple, located in Konda District, South Konawe Regency. Data collection is done by observation, interviews, documentation. The data were analyzed descriptively, which was then analyzed using SWOT analysis. The results showed that the strength factor in UD. Simple is greater than weakness, and the opportunity factor is greater than the threat factor. The results of the analysis on the SWOT diagram show the position in quadrant I, which means that home industries tend to be profitable to use their internal strengths by using their strengths and opportunities to minimize weaknesses and threats, so that is the right strategy for marketing banana chips at UD. Simple during the Covid-19 pandemic in Konda District, it is to maintain the quality of durable banana chips products to retain regular customers, increase demand for banana chips products with relatively sufficient sources of capital, develop variants of banana chips flavors, utilize social media to increase marketing in Indonesia. the Covid-19 pandemic. The results of the analysis on the SWOT diagram show the position in quadrant I, which means that home industries tend to be profitable to use their internal strengths by using their strengths and opportunities to minimize weaknesses and threats, so that is the right strategy for marketing banana chips at UD. Simple during the Covid-19 pandemic in Konda District, it is to maintain the quality of durable banana chips products to retain regular customers, increase demand for banana chips products with relatively sufficient sources of capital, develop variants of banana chips flavors, utilize social media to increase marketing in Indonesia. the Covid-19 pandemic. The results of the analysis on the SWOT diagram show the position in quadrant I, which means that home industries tend to be profitable to use their internal strengths by using their strengths and opportunities to minimize weaknesses and threats, so that is the right strategy for marketing banana chips at UD. Simple during the Covid-19 pandemic in Konda District, it is to maintain the quality of durable banana chips products to retain regular customers, increase demand for banana chips products with relatively sufficient sources of capital, develop variants of banana chips flavors, utilize social media to increase marketing in Indonesia. the Covid-19 pandemic.